THE INFLUENCE OF SEMEN FREQUENCY COLLECTION ON CONCENTRATION AND SPERMATOZOA ABNORMALITIES OF QUAIL - Bebas, Wayan; Permana, Komang Gita; Trilaksana, I Gusti Ngurah Bagus; Laksmi, Desak Nyoman Dewi Indira (Buletin Veteriner Udayana; Vol. 10 No. 2 Agustus 2018DO - 10.24843/bulvet.2018.v10.i02.p16, 2018)
The aims of this study are to determine the influence of collecting frequency against concentration and spermatozoa abnormalities of quail. This study used a completely randomized design (CRD) with 3 treatment groups, is collecting sement at 2, 3 and 4 days intervals. Each treatment is repeated 9 times. Observations were made on the concentration of spermatozoa (10 7 cells/ml) and abnormalities of spermatozoa (%). The data were analyzed using analysis of variance (ANOVA) if there are significantly different (P<0.05) followed by Duncan test. The results showed the concentration of spermatozoa in each treatment respectively 39.00±5.148 x10 7 cells/ml; 59.49±1.878 x10 7 cells/ml; 59.11±2.028 x10 7 cells/ml. Abnormality in each treatment was 14.22±1.394%; 7.22±1.202%; 7.49±1.130%. The frequency of ejaculation was statistically significant (P<0.05) against the concentration and spermatozoa abnormalities of quail.